Isu Megapolitan Jabodetabekjur Dalam Konteks Pengelolaan Pembangunan dan Revisi UU No. 34/1999 - Zulkaidi, Denny (Journal of Regional and City Planning, 2006)
Jabodetabekjur Megapolitan issue which was launched at the same time with the revision of Law No. 34/1999 concerning The Government of DKI (Daerah Khusus Ibukota, Special District Region) Jakarta has raised pros and cons from different parties. Regencies and municipalities next to the DKI Jakarta immediately support this concept, while the Province of West Java and the Province of Banten respond differently against the concept. The emergence of pro and con, and inappropriate perception and responds toward this concept mainly come from lack of understanding of the concept, undeliverable the content of megapolitan concept completely, and lack of communication between the Province of DKI Jakarta and related provincial and regency/municipal authorities. The issue can be discussed from three different views. First, as rapidly developed urban areas growing into a large continuous urban area, the Jabodetabekjur region requires the megapolitan management concept to manage development within a large scale urban area. Second, as the implementation of â lex specialis derogat legi generalisâ principle of the Law No. 32/2004 concerning Regional Government, the revision of Law No. 34/2999 concerning the Government of DKI Jakarta should focus on the internal governmental system within the DKI Jakarta only, separated from the megapolitan issue. Megapolitan issue should be regulated by a specific regulation based on the Law No. 24/1992 concerning Spatial Planning, Government Regulation No. 47/1997 concerning National Spatial plan, or Presidential Decree draft of Jabodetabekpunjur. Third, in responding to the reactions of immediate regencies and municipalities of DKI Jakarta toward the Jabodetabekjur megapolitan issue, the Province of West Java and Banten should improve their governmental service performances and develop a breakthrough thinking based on West Java public interest and public welfare in general, and the people living around DKI Jakarta in particular.Keywords: Megapolitan, Jabodetabekjur, development management, Regional Government Law, Regional Government Law of DKI Jakarta.